The change of temperature on the shear strength of permanent soft-liner on acrylic resin - Waloejo Noegroho; Utari Kresnoadi; Adi Subianto (Dental Journal (Majalah Kedokteran Gigi), 2006)
The characteristics of dental material such as solubility and water resorption, the use of adhesive, storage condition or used as thermo cycling or elevated-temperature are factors that can effect bond strength. The purpose of this study was to investigate the change of temperature on the shear strength of permanent soft liner on acrylic resin. Twenty-four specimens were divided into 3 groups and immersed in water at: 5 °C, 37 °C and 55 °C. Autograph AG 10 TE Shimadzu was used to determine the shear strength. The statistical test (ANOVA and LSD); showed that there were significant differences between temperature groups. The shear strength of 37 °C was higher than the temperature of 5 °C and 55 °C.